Environmental Implications of Autonomous Vehicles : A Case Study on Autzu’s Ridesharing Model and CO2 Reduction - Jiri Jilek (International Journal of Scientific Research in Science and Technology, 2024)
Regarding the environmental impact of Ridesharing integrated with AVs, this paper examines the work done to identify substantial CO2 reductions possible with AV use. Drawing on the trends in the shift to AV and on the adoption of EVs, the paper estimates the potential green effects of swapping ICE vehicles for autonomous electric ones. We also discuss updates in AVs, infrastructure issues, solar power options for charging stations, future forecasts of global CO2 emissions, and the felt shortcomings of this study. The study shows that although AVs may hold the key to the dramatic reduction in emission levels, their potential is only as good as the infrastructure and policies in place, as well as a few technological constraints.
Keywords: Environment; Autonomous Vehicles; Ridesharing; CO2 Reduction; Carbon Emission